4D seismic monitoring of small CO 2 injection: Results from the Ketzin pilot site (Germany) - Lüth, S.; Ivanova, A.; Juhlin, Christopher; Juhojuntti, N.; Kashubin, A.; Bergmann, P.; Götz, J. (2011)
As a response to global warming, mainly caused by increasing atmospheric concentration of carbon dioxide, and growing energy consumption world-wide, Carbon Capture and Storage (CCS) is regarded as one option to ensure safe energy provision and mitigation of climate change in the near future. Although the technology of geological storage of carbon dioxide has been applied in the framework of oil and gas exploration for over a decade now, it has not yet reached a mature state for, e.g., coal fired power plants or energy intensive industries. One of the first pilot sites for onshore storage of CO2 in a deep saline aquifer has been deployed at the town of Ketzin (Germany). The characteristics of the site are not typical for future industrial demonstration projects which will be operated in much larger dimensions and in deeper reservoirs. However, the storage operations at the Ketzin site are combined with a wide range of geophysical, geochemical and microbial monitoring methods which are tested for their applicability on larger storage sites. Seismic monitoring plays a crucial role in this context as it has proven to deliver the most comprehensive information on the spatial distribution of the injected CO2 in the reservoir. The first 3D seismic repeat survey was acquired after approximately 14 months of injection and delivered high resolution images of the lateral distribution of the injected CO2. A mass estimation of the CO2 imaged by the seismic measurements, using petrophysical and borehole logging results showed that the seismic surveys were able to image approximately 93-95% of the injected CO2. The remaining 5-7% are assumed to be undetected within the reservoir, or dissolved in the reservoir brine and thus undetectable for seismic measurements.